Analisis Faktor Penyebab Terjadinya Eksploitasi terhadap Anak Buah Kapal (ABK) Asing di Sektor Perikanan Internasional oleh PT. Pusaka Benjina Resources (PBR) Tahun 2015 - Dwiska, Felina; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
In 2015, PT. Pusaka Benjina Resources (PBR) operated in Aru Islands, Maluku, Indonesia has exploited its 1.242 foreign crew members, mainly from Myanmar, Thailand, Cambodia, Laos and Indonesia. The crews were exploited in various forms, such as worked for 12-24 hours in a day, being paid under minimum wage, physically tortured and even murder that was proved by the existence of foreign crew members’ graveyard. This research aims to determine factors that causing PBR to commit such exploitation acts. This research uses the theory of Primitive Accumulation from Marxism and theory of Global Value Chain by Gary Gereffi. The method uses for this research is qualitative with explanative type. This research proves that the factors causing PBR to exploit the crews was because the demand of U.S market which also supported by the loophole on its national law, PBR aimed to gain much profit, and the lack of control by the states that involved in PBR’s value chain.